2018
DOI: 10.1111/gcb.14065
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution in the coccolithophore Gephyrocapsa oceanica following 1,000 generations of selection under elevated CO2

Abstract: Coccolithophores are important oceanic primary producers not only in terms of photosynthesis but also because they produce calcite plates called coccoliths. Ongoing ocean acidification associated with changing seawater carbonate chemistry may impair calcification and other metabolic functions in coccolithophores. While short-term ocean acidification effects on calcification and other properties have been examined in a variety of coccolithophore species, long-term adaptive responses have scarcely been documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…These differing trends between the present work and previous studies may be attributed to either changes in the thickness of the coccolith layer surrounding the cells, or to the temperature range used. The coccoliths of E. huxleyi can play a protective role against UVR by either strongly scattering light, or by physically shading intracellular organelles (Xu et al, 2016;Voss et al, 1998). In our results, the cellular PIC at 20 • C was only half of that at 15 • C. As cellular PIC is an indicator of the amount of coccoliths on the exterior of the cell, this suggests that the cells grown at 20 • C had a substantially thinner coccolith layer and consequently received much more UV radiation, leading to increased photosynthetic damage compared with cells grown at 15 • C. At 24 • C, the thermal reaction curves suggested that this temperature level was already close to the upper tolerance limit for growth in E. huxleyi PML B92/11, with HCgrown cells suffering more thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…These differing trends between the present work and previous studies may be attributed to either changes in the thickness of the coccolith layer surrounding the cells, or to the temperature range used. The coccoliths of E. huxleyi can play a protective role against UVR by either strongly scattering light, or by physically shading intracellular organelles (Xu et al, 2016;Voss et al, 1998). In our results, the cellular PIC at 20 • C was only half of that at 15 • C. As cellular PIC is an indicator of the amount of coccoliths on the exterior of the cell, this suggests that the cells grown at 20 • C had a substantially thinner coccolith layer and consequently received much more UV radiation, leading to increased photosynthetic damage compared with cells grown at 15 • C. At 24 • C, the thermal reaction curves suggested that this temperature level was already close to the upper tolerance limit for growth in E. huxleyi PML B92/11, with HCgrown cells suffering more thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae are known to exhibit evolutionary responses to elevated CO 2 over hundreds of generations, including downregulated CCMs in a green alga (Collins et al, 2006), irreversible capacity of reduced calcification in a coccolithophorid (Tong et al, 2018), smaller cell size and decreased respiration and photosynthesis in a model diatom (Li et al, 2017), and increased cellular N/C ratio in E. huxleyi (Jin et al, 2013). The evolutionary response of a diazotroph to OA treatment led to irreversible enhancement of growth and N 2 fixation over hundreds of generations, driven by "genetic assimilation" of plastic traits into adaptive ones (Hutchins et al, 2015;Walworth et al, 2016a).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The coccolithophore E. huxleyi, a calcifying phytoplankton, has been shown to adapt to high CO 2 conditions in marine systems within 500 generations (Lohbeck, Riebesell, Collins, & Reusch, 2013;Lohbeck, Riebesell, & Reusch, 2012). Another coccolithophore species, Gephyrocapsa oceanica, did evolve under high CO 2 , although it is not clear that observed changes were an adaptive response to CO 2 (Tong, Gao, & Hutchins, 2018). Beyond calcifying phytoplankton, the evolutionary implications of elevated CO 2 for marine phytoplankton, and thus its potential effect on the predictability of changes in competition and community composition, is not well resolved.…”
Section: Plasticity and Evolutionmentioning
confidence: 99%